The IMML VDE: models, languages and tools to develop interactive systems. (2nd May 2008) - Leite, Jair C.; Sousa, Lirisnei
In this paper, we present a communication-oriented user interface design language to guide the design of interactive systems. Our approach is motivated by semiotic engineering, a theory of human?computer interaction that assigns to both designers and users the same role in an overall communicative process. We have developed a communicative-oriented set of models, languages and tools to help the development of interactive systems. The Interactive Message Modeling Language (IMML) Visual Development Environment (VDE) is composed of semantic models, the IMML and Visual IMML languages, and tools to translate from a specification to a final user interface. IMML is a markup language to specify an interactive system. Visual IMML is an UML profile to the IMML. The tools translate the IMML specifications to browser-based user interfaces. Our approach is also a methodological tool that attempts to structure a solution space for designer?user communication considering the semiotic engineering theory.